A randomized, placebo-controlled, double-blind trial to evaluate efficacy and safety of Shen-Yuan-Dan capsules, a traditional Chinese medicine, for treatment of peri-procedure myocardial injury following percutaneous coronary intervention - Xiang Li; Ying Zhang; Hong-Xu Liu; Ju-Ju Shang; Qi Zhou; Ai-Yong Li; Xiao-Lei Lai; Wen-Long Xing; Si-Han Jia (Elsevier, 2022)
Background: Peri-procedural myocardial injury (PMI) is a common complication of percutaneous coronary intervention (PCI), which cannot be entirely avoided using available treatments. The findings of earlier research have shown that Shen-Yuan-Dan (SYD) capsules, a traditional Chinese medicine, can potentially alleviating PMI. This study aimed to confirm further this hypothesis in a rigorous, well-designed randomized controlled study. Methods: Our clinical trial was randomized, double-blinded, and placebo-controlled. A total of 181 patients with unstable angina (UA) undergoing elective PCI were randomized to pretreatment with SYD or a placebo under the basis of conventional treatment; 87 patients were pretreated with SYD (4 capsules, 3 times a day, with a further 4 capsules 2 h before PCI) 3 days before the procedure, and 94 patients were given a placebo. No patients received reloading statins before PCI, and SYD or placebo was maintained for 1 month after PCI. The primary endpoint was the incidence of PMI. The secondary endpoint was calculating the incidence rate of all 30-day major adverse cardiovascular events (all-cause mortality, non-fatal myocardial infarction, unplanned revascularization). The safety outcomes, including abnormalities in electrocardiogram and serum biochemical examinations caused by drug use, were also tested. Results: The levels of creatine kinase-myocardial band (CK-MB) in both the SYD and placebo groups were increased at 4 h and 24 h after PCI compared with before the procedure (P < 0.05). The incidence rate of PMI in the SYD group (10.3 %) was lower than that in the placebo group (34 %) (absolute difference, 23.7 % [95 % CI, 11.7-34.8 %], P < 0.01). After taking SYD, the relative risk reduction (RRR) and absolute risk reduction (ARR) were 69.7 % and 24.3 %, respectively; further, number needed to treat (NNT) was 4.2. The 30-day major adverse cardiovascular event (MACE) rate was not statistically different between the SYD and placebo groups (6.9 % vs. 9.6 %, P = 0.352). There were no abnormal situations during the trial. Conclusion: These findings showed that pretreatment with SYD could safely reduce the incidence rate of PMI in patients with UA undergoing elective PCI. Further study on the effects of SYD and how it can improve adverse cardiovascular events outcomes is needed.